Educational Game Media as a 21st Century Science Learning Innovation: A Bibliometric Review - Ecyclovira Rizki Aini; I Made Astra (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The development of digital technology has encouraged the use of game-based learning media as an innovation to improve the effectiveness of physics learning, which is often considered difficult by students. This study aims to comprehensively examine the effectiveness of game-based learning media in physics learning. Methods: Research used is a Systematic Literature Review (SLR) that analyzes various studies on the implementation of game-based learning in physics education. Results: The study involved researching and analyzing 20 scientific articles related to the application of games as learning media for science. The results showed that the use of game-based media can improve students' understanding of scientific concepts, motivate them to learn, and increase their participation in the learning process. Effectively designed games can create a fun and challenging learning experience, allowing students to apply science concepts in a relevant context. In addition, factors such as providing appropriate feedback, adjusting the level of difficulty, and incorporating social interaction in the game also play a role in enhancing the effectiveness of game-based learning media. Further research is needed to deepen understanding of how to optimize the use of game media in physics learning. Novelty: The novelty of this study lies in a comprehensive synthesis of the effectiveness of game-based learning media in physics learning, while identifying its potential for development as an innovative learning strategy that integrates digital technology and 21st-century competency needs.